2020
DOI: 10.1016/j.bmc.2020.115792
|View full text |Cite
|
Sign up to set email alerts
|

A look around the West Indies: The spices of life are secondary metabolites

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 119 publications
0
1
0
Order By: Relevance
“…Recently, in 2020, Zhang et al summarized by structural features and biological activities 165 marine polypropionates reported from 1999 to 2020 [9]. A. Demeritte and W. M. Wuest, in 2020, reported a general review of a small selection of different kinds of Caribbean secondary metabolites, including polyketides, peptides, alkaloids, terpenes, and glucolipids [10]. One of the most recent and extended reviews summarizes all of the marine natural products reported in the literature during 2019 [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in 2020, Zhang et al summarized by structural features and biological activities 165 marine polypropionates reported from 1999 to 2020 [9]. A. Demeritte and W. M. Wuest, in 2020, reported a general review of a small selection of different kinds of Caribbean secondary metabolites, including polyketides, peptides, alkaloids, terpenes, and glucolipids [10]. One of the most recent and extended reviews summarizes all of the marine natural products reported in the literature during 2019 [11].…”
Section: Introductionmentioning
confidence: 99%